Urartian Art: its Distinctive Traits in the Light of New Excavations - van Loon, Maurits Nanning (1960)
1960; sous la direction de A. A. Kampman et Machteid J. Mellink; I. Outline of the History of Urartu; II. Pottery; III. Architecture; IV. Painting; V. Sculpture and Decorative Stonework; VI. Metal work; VII. Ivory, Bone and Woodwork; VII. Cylinder and mostly stamp Seals; IX. Conclusion.